Description of a low‐cost picture archiving and communication system based on network‐attached storage. Issue 3 (20th January 2022) - Costanza, Dario; Coluccia, Pierpaolo; Castiello, Erica; Greco, Adelaide; Meomartino, Leonardo
Abstract: High costs for installing, maintaining, and updating a standard picture archiving and communication system (PACS) can be prohibitive for small/medium‐sized veterinary facilities. The aims of this prospective, exploratory study were to describe the design, implementation, and author experiences for 1 year's use of a low‐cost PACS based on network‐attached storage. The system described here was easily installed and resiliently stored redundant copies of data. It excellently balanced data recovery, system speed, security, and available memory for storage. A virtual private network also allowed off‐site data review. This system can also be used for future off‐site backup of data in the cloud.